The challenge to Christian missions: missionary questions and the modern mind - Welsh, R. E. (H.R. Allenson Ltd, 1906)
I. Introductory: Where the question presses.--II. Political complications: Is the missionary the troubler of the peace?--III. Many races many religions: "East is East and West is West."--IV. God in every system: The cosmic light and dark.--V. Liberal thought and heathen destinies.--VI. Can the missionary motive survive: Does liberal thought cut the nerve of missions?--VII. Chequered results: "Counting the game."--VIII. Chequered results: "The mission-made man."--IX. The men and their methods.--X. The aim: The coming kingdom.--XI. The return-value of missions.--Appendices: A. The Powers and the priests in the East. B. Checks to progress in India